Pengembangan Digitalisasi Melalui Branding Wisata Di Desa Wisata Pekunden - Bosdon Andre Gevril Sinaga; Aida Maqbullah; Gigih Rafif Suthanto; Wina Taskia Aulia; Putriana Setyaningtyas Fadilah; Irfan Muhaimin; Dini Nurjannah; Della Nanda Puspitararas; Ronald Haryanto; Najmudin Najmudin (Universitas 45 Surabaya, 2023)
The purposes of this activity are to contribute in developing Pekunden tourism village, to train adaptability of students to local culture and interaction with all parties, and to apply the knowledge and expertise acquired during in college. The partners of this activity are several parties related to the tourism village of Pekunden Village, Banyumas District, Banyumas Regency with an activity period of one month starting on November 17 2022. The outputs of the program implemented include Instagram reels, video promotions of tourism village, and website development. The conclusion from this activity is that Pekunden tourism village has a higher potential could be developed. Various potentials could be introduced more broadly through a variety of innovation updates by utilizing information technology, one of which is through the development of social media. The development of this tourism village involves various parties such as the village government, pokdarwis, working group, and local community. The role of various parties still needs to be increased in introducing this tourism village so that many people could be interested to visit the tourism village.